ANALISIS SOSIO-YURIDIS TERHADAP PENGGUNAAN LAMPU UTAMA SEPEDA MOTOR PADA SIANG HARI: SOCIO-JURIDIC ANALYSIS OF USE MAIN LIGHTS OF MOTORCYCLES AT DAYTIME - Alif Masselomo, Andi Akhmad; Renggong, Ruslan; Madiong, Baso (Faculty Of Law Bosowa University, 2021)
This research aims to analyze and comprehend the law enforcement towards motorist that did not turn their main lights on during the daytime motorists refused to turn their main lights on the during the daytime.Secondly,this research purposed to acknowleddge the factors of why during the daytime motorists refused to turn their msin lights on.This research used several methods,consist of interview,uestionnaire,observation considering referred laws. The result of fthis research showed the law enforcement took actions in pre-emptive efforts,preventive efforts,and represie efforts.Howeever,those efforts did not done effectively considering the facts that there are still so many motorists in Makassar refused to turn their main lights on during the daytime.Whereas,the factors are the disagreement of motorists to obey that rules,there are many elements of society that do not understand and comprehend the rules,there law enforcer that still uneffectively wroked,the lack of supporting facilities in enforcing the usage of main lights during the daytime.